Avoid XML schema wildcards for Web service interfaces - Pasley, J. (IEEE internet computing, 2006)
Developers risk negative side effects when they attempt to make Web services interfaces extensible without understanding the context in which various mechanisms are applied. Given the overuse and misapplication of the HTML example, developers often litter their interfaces with XML Schema wildcards. This increases complexity and results in ambiguous interface definitions. A more appropriate versioning strategy for Web services development can help developers avoid these problems